2002
DOI: 10.1345/aph.1a289
|View full text |Cite
|
Sign up to set email alerts
|

FDA Adverse Event Reports on Statin-Associated Rhabdomyolysis

Abstract: Compared with the other statins, simvastatin and cerivastatin were implicated in a relatively higher number of reports. Because of the various limitations of a spontaneous reporting-system database, caution is urged when interpreting the relative number of cases reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
165
0
12

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(181 citation statements)
references
References 21 publications
4
165
0
12
Order By: Relevance
“…Statins, especially simvastatin and cerivastatin, are known to cause rhabdomyolysis Omar and Wilson (2002); www.fda.gov/ bbs/topics/answers/ans00876.html Sorivudine/5-fluorouracil (5-FU) interaction, leading to severe or fatal gastrointestinal and bone marrow toxicities. Soruvidine was withdrawn from the market in 1993…”
Section: Drug-drug Interaction Mechanism Of Interactions Referencesmentioning
confidence: 99%
“…Statins, especially simvastatin and cerivastatin, are known to cause rhabdomyolysis Omar and Wilson (2002); www.fda.gov/ bbs/topics/answers/ans00876.html Sorivudine/5-fluorouracil (5-FU) interaction, leading to severe or fatal gastrointestinal and bone marrow toxicities. Soruvidine was withdrawn from the market in 1993…”
Section: Drug-drug Interaction Mechanism Of Interactions Referencesmentioning
confidence: 99%
“…In large clinical trials statin-induced myopathy and rhabdomyolysis have been reported in 0.1-0.5 and 0.02-0.2% of patients, respectively [6][7][8][9]. The mode of action for muscle toxicity is not known, but risk factors for this adverse reaction include high statin dose/serum concentration, female sex, age and drug-drug interactions [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Simvastatin, lovastatin and atorvastatin are all metabolized by cytochrome P450 3A4 (CYP3A4), whereas pravastatin and fluvastatin mainly have other eliminating pathways [13]. Many agents are inhibitors or inducers of CYP3A4, and the general interaction potential of simvastatin, lovastatin and atorvastatin is therefore higher than for other statins [8,10]. Of the CYP3A4 statins, simvastatin and lovastatin are more sensitive than atorvastatin in terms of relative increase in serum concentration during co-administration of CYP3A4 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Our review focused on chronic-use medications known to increase risk for HMG-CoA inhibitor (statin) myopathy. 8,[11][12][13][14][15][16] Patients prescribed short-term, potent CYP3A4 inhibitors were excluded from our review. Patients who receive short-term therapy with potent CYP3A4 inhibitors (e.g., clarithromycin, erythromycin, itraconazole, and ketoconazole) should be counseled to temporarily withhold their statin therapy.…”
Section: Frequency Of Simvastatin Prescriptions With Potentially Intementioning
confidence: 99%
“…8,12,13 Several medications have been identified that increase the risk of myopathy when administered concurrently with statins, primarily by decreasing the metabolism of the statin (Figure 2). 8,[14][15][16][17][18] Although these drug-drug interactions are well documented as increasing risk for myopathy, published studies documenting the frequency of prescribing interacting drugs are lacking. Einarson and colleagues 19 studied the extent of drug interactions and health care utilization in patients receiving statins.…”
mentioning
confidence: 99%